Serat Centhini (Suluk Tambangraras) - Kanjeng Gusti Pangeran Adipati Anom Amengkunagara (Yayasan Centhini, 1989)
tr, jil.1-4; jil.5-7; jil.8-10; jil.11-12=c.1/stoc6, jl.1-2; jl.3-4; jl.5-7; jl. 8-10; jil.11-12=c.1